Analisis Kesulitan Belajar Mahasiswa pada Mata Kuliah Kalkulus Peubah Banyak Di STKIP PGRI Pasuruan - Dewi Nurmalitasari (FKIP Universitas Islam Jember, 2017)
This research aims to describe learning difficulty and the factors causing of calculus multivariate difficulty in STKIP PGRI Pasuruan based on Taksonomi Bloom C1 till C4. The data are collected by using purposive sampling and obtained from written test, interview, questionnaire, and observation. The result showed that the highest grade of learning difficulties are application (C3) and analysis (C4) with an average 84% while there are 7 factors such as health, fatigue, lecturer interaction, learning instrument, media, calculus multivariate course, and motivation.Keywords: Learning difficulties, calculus multivariate